Surgery for Killian-Jamieson diverticulum: a report of two cases - Kohei Saisho; Satoru Matono; Toshiaki Tanaka; Naoki Mori; Haruhiro Hino; Masahiro Fujisaki; Masashi Nakagawa; Fumihiko Fujita; Yoshito Akagi (Surgical Case Reports)
Abstract Background Killian-Jamieson diverticulum (KJD) is a rare diverticulum arising from a muscular gap in the anterolateral wall of the proximal cervical esophagus. The first choice of treatment for KJD remains controversial due to its rare incidence. Here, we report two cases of KJD for which we performed different surgery: diverticulectomy in one case and diverticulopexy in the other. Case presentation Case 1 involved a 58-year-old woman presenting progressive pharyngeal discomfort for the past year. She was diagnosed as KJD using endoscopic and radiographic findings. She underwent diverticulectomy with cricopharyngeal and proximal esophageal myotomy. Staple line leakage developed at 1 month after surgery and was successfully treated conservatively. At 5 months after surgery, she was asymptomatic. Case 2 involved a 77-year-old woman presenting dysphagia for the past 2 years. She had a history of bilateral breast cancer and had hypertension, asthma, and osteoporosis. Taking her age and medical history into account, we selected diverticulopexy with cricopharyngeal and proximal esophageal myotomy. The postoperative course was uneventful. At 2 years after surgery, she remained free of dysphagia. Conclusion The first choice of surgery for KJD is diverticulectomy. In a high-risk patient, diverticulopexy is a reasonable treatment. We recommend the addition of myotomy as a part of any surgical treatment.